2019
DOI: 10.1634/theoncologist.2019-0473
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab and Gemcitabine for Advanced Pancreatic Cancer: A Phase Ib Study

Abstract: Background. Pancreatic ductal adenocarcinoma (PDAC) remains resistant to chemotherapy and immunotherapy individually because of its desmoplastic stroma and immunosuppressive tumor microenvironment. Synergizing cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) immune checkpoint blockade with chemotherapy could overcome these barriers. Here we present results of a phase Ib trial combining ipilimumab and gemcitabine in advanced PDAC. Materials and Methods. This was a single-institution study with a 3 + 3 dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 40 publications
1
90
0
1
Order By: Relevance
“…Thus, patients displaying high diversity of TCR clonality before treatment followed by high proliferation of specific clones after ipilimumab therapy were associated with better survival than patients having a more unfavorable TCR repertoire at baseline (median survival 8.66 months vs. 4.28 months) [84]. Another phase 1b study involving the combination of ipilimumab and gemcitabine concluded an overall survival of 6.9 months for 21 patients with an advanced (previously pretreated) disease with a tolerable toxicity profile [85]. Furthermore, patients benefited from combined therapeutic approaches as the additive effect of GVAX, PD-1 inhibitors, or chemotherapeutic drugs became evident.…”
Section: Application Of Immune Checkpoint Inhibitors In Pdacmentioning
confidence: 99%
“…Thus, patients displaying high diversity of TCR clonality before treatment followed by high proliferation of specific clones after ipilimumab therapy were associated with better survival than patients having a more unfavorable TCR repertoire at baseline (median survival 8.66 months vs. 4.28 months) [84]. Another phase 1b study involving the combination of ipilimumab and gemcitabine concluded an overall survival of 6.9 months for 21 patients with an advanced (previously pretreated) disease with a tolerable toxicity profile [85]. Furthermore, patients benefited from combined therapeutic approaches as the additive effect of GVAX, PD-1 inhibitors, or chemotherapeutic drugs became evident.…”
Section: Application Of Immune Checkpoint Inhibitors In Pdacmentioning
confidence: 99%
“…Multiple clinical trials have tested the combination of checkpoint inhibition and chemotherapy in PDAC patients [ 175 ]. Published studies have reported on the anti-CTLA-4 antibodies tremelimumab and ipilimumab, respectively [ 227 , 228 ], as well as the anti-PD-1 antibody pembrolizumab [ 229 ]. However, most of these trials are phase I studies, and no conclusive beneficial evidence has been reported [ 176 ].…”
Section: Immunotherapy In Pdacmentioning
confidence: 99%
“…When PD-1/CTL4 inhibitors combined with commonly used chemotherapeutic agents such as Nab-paclitaxel, gemcitabine, carboplatin, and FOLFOX improved overall survival [47]. Remarkably, therapeutic procedures using a combination of immune checkpoint inhibitors with radiotherapy or chemotherapy have shown significant outcomes [185,186].…”
Section: Immunotherapy For Pancreatic Cancermentioning
confidence: 99%